A new urea adducts method for PUFA concentration using green food grade solvents and avoiding ethyl carbamate formation. (30th October 2022) - Vázquez, Luis; Sánchez-Moyano, Mario; de la Iglesia, Lorena; Reglero, Guillermo; Torres, Carlos F.
Highlights: A new methodology for concentration of PUFA by urea complexation has been developed by using green food grade solvents. Propionic acid and α-pinene were efficient as substitutes of ethanol and hexane, respectively. There is no detectable formation of potentially toxic ethyl carbamates. The procedure was tested on different raw materials and solvent reutilization was performed. Abstract: This study aimed to selectively enrich stearidonic acid (SDA) together with γ-linolenic acid (GLA) in Echium plantagineum oil by urea complexation. The complexation process at room temperature was carried out replacing common organic solvents, such as hexane and ethanol, by alternative compounds, included in Green Solvent and Food Grade categories, adapting this process towards the principles of Green Chemistry . This substitution was also intended to avoid the generation of the toxic compound ethyl carbamate. Among all the solvents studied, the mixture propionic acid and α-pinene provided the best results, leading to a final product comprised of ∼99% of PUFA, with ∼45% SDA (∼14% in the original oil), and without apparition of ethyl carbamate. The procedure was tested on other raw materials (salmon and microalgae oils). The solvent was efficiently recuperated from the liquid phase (∼87% recovery) and reutilized once with almost identical results.